Subclinical inflammatory diseases of the pelvic organs: chronic endometritis - N I Tapilskaya; S A Karpeev; I V Kuznetsova (IP Berlin A.V., 2014)
The economic costs of treating infertility using assisted reproductive technologies are a burden even for advanced Western countries.In infertility patients with long and unsuccessfully treatment history, where all available methods, including assisted reproductive technology are present, chronic endometritis is diagnosed in 60% of cases. Overview of research on chronic endometritis, suggests that endometrium contaminated by microorganisms with confirmed subclinical inflammation is the cause of the reduction in fertility. Identification of a microbial agent in endometritis in routine outpatient practice is not mandatory, as the international experience, including research with a high level of evidence proves the expediency of empirical therapy, based on the minimum clinical criteria, because, otherwise, the consequences for the reproductive system may be irreparable. Preventive antibiotic therapy in patients with pre-conception infertility and recurrent miscarriage is an effective way of preventing reproductive losses. Josamycin is the drug of choice for these conditions due to broad-spectrum, high efficacy against intracellular agents and anaerobic microbiota, favorable safety profile, as well as additional systemic anti-inflammatory and immunomodulatory effects.